Length-weight relationship and relative condition factor in Sillago sihama (Forsskal) from Mandapam region - Jayasankar, P (Indian Journal of Fisheries, 2011)
Sillago sihama forms about 60% of allsillaginids commercially exploited in the gulfof Mannar and Palk Bay landing centres ofRamanathapuram district in Tamil Nadu(Jayasankar 1991). Only a preliminary studyon the length-weight relationship andcondition factor of S. sihama was made byRadhakrishnan (1957) from Mandapam area.Later work (Jayasankar 1991) showed amarked difference from Radhakrishnan'sresults on condition factor. This study reexaminsthe issue